Quality teaching frameworks and arts education: Seeking a compatible approach. Issue 6 (1st November 2020) - Fleming, Josephine; Gibson, Robyn; Anderson, Michael; Martin, Andrew J.
ABSTRACT: As school education systems worldwide adopt standardized performance measures, teacher effectiveness frameworks have become more influential. This article draws on Australian mixed methods research that aimed to understand the processes behind quality arts pedagogy. Following an in-depth quantitative study, nine high-performing case study arts classes were selected, spanning dance, drama, media arts, music and visual arts. The Quality Teaching Framework (QTF), based on authentic pedagogy, was used to observe and to analyse twenty-seven arts lessons, three per case study. This framework, trialled and validated in prior large-scale research, was adopted by the New South Wales public education system. While the framework's categories were useful in detecting aspects of quality arts pedagogy, we also observed shared practices that were absent from the QTF. The article focuses on these absences. To support the creation of original work, these classes included generative processes not adequately explained by the framework, which made no direct reference to creativity. This led the research team to: (1) question the extent to which generic standardized (GS) teaching frameworks explain the dynamics of arts classrooms, and (2) reflect on whether certain processes are not easily categorized within standardized measures and whether this can lead these processes to be undervalued.